(untitled) (Bangladesh Pharmaceutical Journal, 2023)
Depression is a pervasive psychiatric disorder worldwide and diarrhea is considered a leading cause of preventable death for infants and children in developing countries. The current study was done to assess in vivo activities of crude methanol extract of Stixis suaveolens fruit, focusing on antidepressant and antidiarrheal effects. The effect on central nervous system (CNS) was examined by recording the onset of sleep and total sleeping time. Besides, castor oil-induced diarrhea in the mice model was followed while evaluating the antidiarrheal effects. Significant (p<0.01) reduction in onset time (64.8 min) as well as in total sleeping time (64.8 min) were recorded between the test groups and the control. The extract, when given orally, also resulted in a significant (p < 0.001) reduction of diarrheal feces induced by castor oil by 71.43%. The in vivo bioassays demonstrated that the crude methanol extract of the fruit of S. suaveolens contains significant antidiarrheal and CNS stimulating actions. However, further vigorous studies are recommended to isolate and characterize the major phytoconstituents from the plant in order to develop the exact mechanism of actions of the plant against various disorders. Bangladesh Pharmaceutical Journal 26(1): 28-35, 2023 (January)